Forest regeneration in secondary forest areas at Morro Grande Forest Reserve, Cotia, SP - Alves, Luciana F; Metzger, Jean Paul (Biota neotropica, 2006)
Notwithstanding its complexity, a more integrated knowledge of the regeneration process in tropical forests subject to natural as well as human disturbance is necessary. Given the great extent of secondary forests in the Neotropics, an important topic to be considered is the potential of secondary forest patches to preserve the biological diversity of old-growth, less disturbed forests. The main objective of this study was to evaluate tree seedling community structure and its potential as source of regeneration in areas of secondary forest within the Morro Grande Forest Reserve (RFMG), one of the most important areas of Atlantic Rain Forest on the Atlantic Plateau. The structure and composition of the tree seedling community was sampled in 1 m super(2) plots randomly placed in three areas of secondary forest. We recognized 106 species among 742 sampled tree seedlings, distributed in 35 families and 69 genera. The richest families (Myrtaceae, Fabaceae, Rubiaceae and Lauraceae) represented 47% of the species total, and the five more abundant species were Myrcia fallax, Ocotea dispersa, Psychotria vellosiana, Psychotria suterella, and Matayba elaeagnoides. Woody species regeneration was predominantly composed of zoochoric and shade tolerant species, characteristics of more advanced stages of Atlantic Rain Forest succession. Tree seedling community did not vary in abundance and size structure, but species composition and richness varied significantly among areas. Our results suggest that woody regeneration in secondary forest areas of the RFMG has a high potential of maintaining tree biological diversity of old-growth forests and, consequently, contributing to forest restoration at the regional scale. Spatial heterogeneity in floristic composition and species richness of the seed rain, as well as of the tree seedling community in secondary forest patches, represent important components that influence the sucessional process and the maintenance of species diversity, therefore acting as sources of recruitment of new individuals and species.